2014
DOI: 10.1016/j.nrl.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación longitudinal con FP-CIT en pacientes con parkinsonismo

Abstract: Serial FP-CIT studies are unnecessary in the large majority of cases, but they may be justifiable in certain clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this context, it would be interesting to perform an evolutionary study in this subgroup of patients, since the rapidly progressive deterioration of the disease could confirm or rule out the existence of MSA at a later stage. In the literature, we found hardly any research on this aspect [16,19,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it would be interesting to perform an evolutionary study in this subgroup of patients, since the rapidly progressive deterioration of the disease could confirm or rule out the existence of MSA at a later stage. In the literature, we found hardly any research on this aspect [16,19,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it would be interesting to perform an evolutionary study in this subgroup of patients, since the rapidly progressive deterioration of the disease, it could confirm or rule out the existence of MSA at a later stage. In the literature, we found hardly any research on this aspect [16,19,36].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous cross-sectional study by our group, qualitative SPECT assessments were found to be accurate in differentiating between the two subtypes. Given that, in this disease, diagnostic errors can occur in the first SPECT assessment (especially in the MSA-C subtype), a serial study would allow for the detection of false negatives or doubtful results and correctly establish the diagnosis [11,15,16,21]. As an example of this, we found in our casuistry a 62-year-old woman with dysautonomic, parkinsonian, and cerebellar symptoms, unresponsive to treatment with levodopa, and it finally turned out to be a case of MSA-C with bilateral striatal involvement (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This makes patient recruitment very difficult and, above all, difficult to establish loyalty for a possible follow-up. For this reason, there are very few neuroimaging follow-up studies, with some being retrospective [15] or having a smaller sample size [13]. It could have been considered to recruit a cohort of healthy patients (as a control group) to study them comparatively with the MSA patients; however, no ethics committee could approve the administration of radionuclides in healthy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation